Characterization of dissolved organic nitrogen in wet deposition from Lake Erhai basin by using ultrahigh resolution FT-ICR mass spectrometry. (August 2016) - Feng, Shuang; Zhang, Li; Wang, Shengrui; Nadykto, Alexey B.; Xu, Yisheng; Shi, Quan; Jiang, Bin; Qian, Weibin
Abstract: Dissolved Organic Nitrogen (DON) of wet deposition in Erhai basin (EWD) was characterized at the molecular level by using electrospray ionization Fourier transform ion cyclotron resonance mass spectrometry (ESI FT-ICR MS). The structure and composition of DON were investigated by the combined ESI FT-ICR MS, UV–Vis absorbance and fluorescence techniques. The FT-ICR MS measurements indicate that a large (∼790) number of organic species present in the wet deposition, in which DON account for 18.3%, with most of DON containing a single nitrogen atom. The typical relative molecular mass of the DON species was found to be in the range of 200–400 Da. Approximately 57.2% of DON species are highly unsaturated (DBE (Double Bond Equivalent) > 5) with the nitrogen- and sulfur-containing species, which are probably represented mainly by active nitrooxy organosulfates, accounting for ∼ 19.3% of the total DON. The low average SUVA254 and A253 /A203 values (0.02 and 0.06, respectively), indicates that the aromaticity of the EWD samples is particularly weak. The average values of E2 /E3 and E4 /E6 in the EWD samples were 6.84 and 1.84, respectively. This is a clear indication of the low degree of humification of EWD samples, in agreement with ESI FT-ICR MS measurements. Our study demonstrates that multiple experimental techniques combined with FT-ICR MS, UV–Vis absorbance and fluorescence can be efficiently used for in-depth studying the DON at the molecular level. Thus it allows us to achieve a deep and insightful understanding of the DON structure and composition. Highlights: DON accounted for 18.3% in EWD samples, with the majority containing only one nitrogen atom. DON in wet deposition showed weak aromaticity but high activity with amino and nitro-sulphate groups. Highly unsaturated substances account for 57.2% of DON in the EWD samples (DBE > 5). DON in Erhai wet deposition were highly unsaturated, which would indicate oxidation reactions and increase risk of deteriorating water.